Mining-based tourism in Sawahlunto National Geopark - Nendi Rohaendi; Revi Timora Salajar; Darius Agung Prata; Oki Oktariadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Determining post-mining land use is a challenging process for mining cities. The new rapid development of geopark is an alternative solution to how to deal with mined land. The objective of the research is to study potential anthropogenic landforms (mining landforms) or geosite as a tourism object in Sawahlunto national geopark. Sawahlunto in west Sumatra province is the oldest coal mining industry. This mining area mostly belongs to state-owned companies in Indonesia. The potential tourism in geoparks will be assessed using the ABC concepts. The method will be useful information for alternative post-mining land use. Primary data were obtained through field observations at Sawahlunto Regency and in-terviews with the stakeholders. Secondary data were collected through desk study in the form of spatial information and policy documents, especially from The Agency of Local Spatial Plan, and The Agency of Culture, Heritage, and Museum of Sawahlunto Regency. Filed observation activities aim to determine the position of geodiversity, biodiversity, and cultural diversity potential using Global Positioning System (GPS) technology. The results of field observational data are processed using Geographic Information System (GIS) software including data inputting, data plotting, and data analysis. Interviews were conducted with ac-tors directly involved in the tourism development of the Sawahlunto Regency such as The Agency of Spatial Planning and The Agency of Culture, Heritage, and Museum of Sawahlunto Regency. The result of the research shows that there are four mining-based tourism zones in Sawahlunto national geopark. The identification of mining-based tourism is broadly useful for the future development of Sawahlunto geopark. However, since there is complexity in terms of the management of geopark, people need to carefully consider spatial plan for geopark area.